Water and Sanitation Access: An Analysis of Households in Indonesia - Sebayang, Lesta Karolina; Diana Sapha; Rokhmad Hidayat (Universitas Negeri Semarang, 2025)
Water and sanitation are critical components in achieving the SDGs. In Indonesia, poor water quality and sanitation have been the primary causes of diarrheal illnesses, resulting in high child death rates. This research investigates the extent to which a community's socioeconomic and demographic characteristics influence the adoption of water and sanitation facilities. Using the logit model analysis method, the data used is from an IFLS5 survey of 14,827 households. The findings indicate that sanitation improvements are linked to household expenditure and toilet use, but piped water availability is related to education and water source location. However, expenditure has no significant effect on the transition from non-piped to piped water sources. Limited access to clean drinking water and sanitation services can pose health risks to the community, socioeconomic status, and the environment. The study provides policy recommendations to expand the coverage of clean water and sanitation services to the community for better household health in Indonesia.